2006
DOI: 10.1210/en.2006-0685
|View full text |Cite
|
Sign up to set email alerts
|

A Pituitary Cell Type Coexpressing Messenger Ribonucleic Acid of Proopiomelanocortin and the Glycoprotein Hormone α-Subunit in Neonatal Rat and Chicken: Rapid Decline with Age and Reappearancein Vitrounder Regulatory Pressure of Corticotropin-Releasing Hormone in the Rat

Abstract: Promiscuous hormone mRNA expression in the pituitary remains poorly understood. We examined by means of RT-PCR and immunostaining whether glycoprotein hormone alpha-subunit (alphaGSU) could be coexpressed with proopiomelanocortin (POMC) in vivo and under pressure of CRH in vitro. Cells coexpressing alphaGSU and POMC mRNA amounted to 2.6% of the cells in ex vivo rat pituitary at birth [postnatal d 1 (P1)], fell to much lower level at P14, and were undetectable in adulthood. In cultured pituitary aggregates of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 83 publications
3
13
0
Order By: Relevance
“…For example, our analysis of Tpit-positive cells during pituitary development led us to identify a very small number of cells (5-20 cells per pituitary) that appeared positive for both Tpit and SF1, and we have shown transcriptional antagonism between these two factors such that the activity of one will ultimately predominate over the other [8]. These observations are consistent with the existence of rare cells positive for POMC and αGSU [17]. Since it appears that cell fate decisions may be established in progenitors after their exit from the cell cycle, the relationship between progenitor cycle exit and differentiation may thus be critical to set these processes in motion.…”
Section: Precursors and Differentiationsupporting
confidence: 82%
“…For example, our analysis of Tpit-positive cells during pituitary development led us to identify a very small number of cells (5-20 cells per pituitary) that appeared positive for both Tpit and SF1, and we have shown transcriptional antagonism between these two factors such that the activity of one will ultimately predominate over the other [8]. These observations are consistent with the existence of rare cells positive for POMC and αGSU [17]. Since it appears that cell fate decisions may be established in progenitors after their exit from the cell cycle, the relationship between progenitor cycle exit and differentiation may thus be critical to set these processes in motion.…”
Section: Precursors and Differentiationsupporting
confidence: 82%
“…As a notable side remark, it is well documented that during certain (patho-)physiological conditions, defined bi- or plurihormonal cells arise of which the function is as yet uncertain, such as cells with GH and gonadotropins before ovulation [6, 18], with ACTH and gonadotropins during the stress non-responsive period [68], with GH and PRL during pregnancy [13, 58], with TSH and ACTH during cold stress [56], with TSH and GH during hypothyroidism [12, 16], and with two or more hormone mRNAs in a combination phenotypical for developmental stage [69, 70] and for trophic stimulus [70,71,72,73]. Often raised hypotheses are that these cells represent either intermediate cells, or multipotential reserve or progenitor cells that differentiate into the desired cell type depending on the hormonal claim of the organism [9].…”
Section: Pituitary Stem Cells: Support From Developmental and (Patmentioning
confidence: 99%
“…For instance, GH + cells are frequently detected just beneath the marginal epithelium in the normal male rat, but disappear after castration to be replaced by some LH + cells [129], suggesting that marginal cells give rise to these endocrine cells. We recently detected double αGSU + POMC + cells in the proximity of the cleft, bihormonal cells hypothesized to represent precursor cells [70]. Obviously, an alternative explanation for all these observations is that marginal cells are supportive or regulatory for the differentiation process, rather than being direct predecessors.…”
Section: Pituitary Stem Cells: Support From Topological Morphologmentioning
confidence: 99%
“…We also showed that N-glycosylation is essential for bioactivity and that certain glycosylated isoforms stimulate PRL mRNA level whereas others have a mitogenic action in lactotrophs (160). That a subpopulation of gonadotrophs is capable of synthesising N-POMC was shown at the mRNA level by means of single cell reverse transcription-polymerase chain reaction (RT-PCR) (161, 162), and some cells also show immunoreactive N-POMC and αGSU colocalisation (161). Nonglycosylated N-POMC, prepared by recombinant synthesis, keeps a specific mitogenic action on lactotrophs (and no other cell types) but its efficacy is weaker and, importantly, the effect is mediated via the γ3-melanocyte-stimulating hormone (MSH) moiety in its C-terminal domain by the melanocortin-3 receptor, whereas glycosylated N-POMC has no action through the melanocortin-3 receptor (163).…”
Section: Gonadotrophs Signal To Lactotrophs Somatotrophs and Corticomentioning
confidence: 99%
“…This phenomenon may pave the way to explore whether urocortins influence the release of αGSU in mammals as well, particularly because cells exist in rat as well as chicken pituitary that express both POMC and αGSU (161). …”
Section: Corticotrophs As Autocrine/paracrine Cells and Targetsmentioning
confidence: 99%